The effects of the COVID-19 pandemic on the treatment of allergic eye diseases. Issue 5 (October 2021) - Leonardi, Andrea; Salami, Elena; Feuerman, Oren Mark; Cavarzeran, Fabiano
Abstract : Purpose of review: To analyze if recommendations given before and during the COVID-19 pandemic are still a valid option for patients suffering of ocular allergy (OA). Recent findings: During the last year many doctors and patients requested suggestions for the treatment of OA patients in COVID-19 time. Most of them were given by phone calls and emails following the recommendations given by Scientific Societies. Summary: Considering the current multiple problems related to the COVID-19 pandemic, OA has not been considered a priority, even though patients need treatments. Topical antiallergic drugs are still the first option to treat all kind of OA, with the addition of topical corticosteroids in the severe forms of vernal and atopic keratoconjunctivitis (VKC and AKC) even in patients at risk of COVID-19. Topical immunomodulation is still recommended in severe forms of VKC and AKC unless the patient is infected. The number of patients treated with these drugs in our Center was similar than previous years. The risk to have a VKC patient affected by COVID-19 is similar to the general pediatric population but with a lower OR. In 2021, still in COVID-time, the management of OA should follow the previous recommendations with an update due to the risk of infection.